PEDAGOGICAL CONDITIONS FOR THE FORMATION OF SUBJECT-METHODICAL COMPETENCE IN FUTURE PHYSICAL EDUCATION TEACHERS (Physical Culture and Sport: Scientific Perspective, 2025)
The article examines subject-methodical competence as a key component in the professional development of future physical education teachers within the context of educational reform and the implementation of a competence-based approach. The purpose of the article is to identify and theoretically substantiate effective pedagogical conditions for the formation of subject-methodical competence in future physical education teachers in the context of modern educational transformations and the requirements of the New Ukrainian School. It is emphasized that subject-methodical competence integrates professional knowledge, didactic skills, pedagogical mastery, and innovative thinking, enabling future specialists to effectively achieve educational goals in modern learning environments. The study identifies and characterizes pedagogical conditions that ensure the effective formation of this competence: integration of theoretical and practical training aimed at aligning the content of professional disciplines with teaching methods; the use of digital educational technologies, which supports the development of digital literacy; the development of soft skills as an essential component of professional culture; motivational and value-based orientation of the educational process, which fosters intrinsic motivation for teaching; and the creation of a learner-centered educational environment that addresses students’ individual educational needs. The article substantiates the need to enhance a practice-oriented approach in teacher training and to introduce innovative methodological tools that facilitate the adaptation of future educators to the realities of professional activity in the context of the New Ukrainian School. The presented concepts can serve as a theoretical and methodological foundation for the modernization of educational programs in the field of physical education.
Keywords: subject-methodical competence; future physical education teacher; competence-based education; pedagogical conditions; soft skills